Mapping digital citizenship among future in professionals - Jakab Enikő; Papp Gabriella; Якоб Еніке; Пап Габріелла (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. The rapid development of digital technologies has fundamentally transformed how people learn, work, communicate and carry out everyday tasks. As more and more aspects of our lives move into the online environment, it becomes increasingly important not only to use digital tools effectively, but also to behave safely, responsibly and ethically in digital spaces. In recent years, the concept of digital citizenship has gained significant attention, as it encompasses the protection of personal data, the critical evaluation of online information, responsible and respectful communication, and the ability to maintain a healthy balance between online and offline activities. IT students play a particularly important role in this context. They are the ones who will design and operate the digital infrastructures of the future, shaping how technology supports society. At the same time, a considerable proportion of them will become IT teachers in secondary education, where they will influence the habits, thinking and attitudes of young people who are already active participants in the digital world. These students represent the next generation of digital citizens, and they will rely on the knowledge and example set by their teachers. Therefore, it is essential that future IT professionals develop not only high-level technical skills but also strong awareness of responsible digital behaviour. The aim of this research is to examine how IT students manage their personal data and digital security, whether they behave critically when consuming online information, and how they support their own digital well-being. It is particularly relevant to understand how they deal with risks such as weak passwords, privacy issues on social media, misinformation or manipulation by digital contentselection algorithms, and how aware they are of the importance of maintaining personal boundaries and healthy screen-time habits. The research is based on an online questionnaire conducted among IT students at the Ferenc Rákóczi II Transcarpathian Hungarian University and provides empirical data on their current level of digital citizenship competencies. The scientific novelty of the study lies in the approach that digital citizenship is examined not only from a technological perspective but also from ethical, social and pedagogical viewpoints. Since IT students will serve both as professionals developing new digital solutions and as future educators guiding younger users, their personal practices have a direct impact on the digital culture of future generations. If they lack sufficient awareness, security knowledge or critical thinking skills, they may not be able to support students effectively in navigating the challenges of the digital world. The expected results of the study can contribute to improving higher education programmes in the field of informatics. They may highlight specific areas where curriculum development or targeted training interventions are needed, especially in relation to digital safety and digital well-being. Strengthening students’ ethical awareness, sense of responsibility and critical thinking can ensure that they become trustworthy and exemplary role models in the digital society. Ultimately, the research supports the development of a modern educational approach that promotes not only technological competence but also responsible participation in the digital environment, which is fundamental for both individual and community well-being in the future.
Keywords: education; digital citizenship; digital safety; data protection; critical information